ANALISIS KINERJA KEUANGAN MENGGUNAKAN RASIO PROFITABILITAS PADA PT XL AXIATA, TBK DAN PT INDOSAT OOREDOO, TBK PERIODE 2011—2016 YANG TERDAFTAR DI BURSA EFEK INDONESIA - ENCEP SAEFULLAH; LISTIAWATI LISTIAWATI; PEGGY MELYANA ABAY (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2018)
AbstractThe purpose of this study is to know the financial performance at PT XLAxiata Tbk and PT Indosat Ooredo Tbk period 2011—2016 by usingprofitability ratio Return on Asset Return (ROA), Return on Equity (ROE)and Net Profit Margin (NPM). The method in this research is qualitativemethod based on postpositivisme philosophy, which is used to test thecondition of nature, and ratio calculation is profitability ratio Return onEquity (ROA) Return on Equity (ROE) and Net Profit Margin (NPM). Inthis study researchers analyze and process financial statements data at PT XLAxiata Tbk and PT Indosat Ooredo Tbk period 2011—2016 by calculating thecalculation on each profitability ratio Return on Equity (ROA), Return onEquity (ROE) and Net Profit Margin (NPM). The results of this studyindicate that the financial performance of PT XL Axiata Tbk and PT IndosatOoredo Tbk period 2011—2016 with profitability ratio Return on AssetReturn (ROA) Return on Equity (ROE) and Net Profit Margin (NPM) stillhave fluctuated value even still at value below industry standard.